Holocene raised beaches at Terra Nova Bay (Victoria Land, Antarctica) - BARONI, CARLO; Orombelli G. (Quaternary Research, 1991)
More than 40 14C dates for raised beaches at Terra Nova Bay ranging from the present to 7505 ± 230 yr B.P. supply minimum or maximum limiting ages that bracket a relative sea-level curve for this part of Victoria Land. Most samples consist of guano and penguin remains collected from abandoned nesting sites on beach deposits. Up to four 14C dates in stratigraphic sequence have been obtained in two soil profiles. Other samples consist of marine shells collected both within and on the surface of raised beaches. All 14C ages for organisms that lived or fed in circumantarctic waters were corrected for a large reservoir effect. The calibrated ages delimit a first relative sea-level curve for Victoria Land. Rates of uplift ranged from about 10 mm/yr following deglaciation to about 2 mm/yr in the last 3 millennia. Widespread presence of Adélie penguin nesting sites suggests that Terra Nova Bay was deglaciated before 7065 ± 250 yr B.P. ( 7059 6439 cal yr B.P.), when environmental conditions in the coastal area were similar to the present ones. © 1991.